Effect of high-molecular-weight glutenin subunit Dy10 on wheat dough properties and end-use quality - Yan WANG; Zhen-ru GUO; Qing CHEN; Yang LI; Kan ZHAO; Yong-fang WAN; Malcolm J. HAWKESFORD; Yun-feng JIANG; Li KONG; Zhi-en PU; Mei DENG; Qian-tao JIANG; et al. (Journal of Integrative Agriculture, 2023)
High-molecular-weight glutenin subunits (HMW-GSs) are the most critical grain storage proteins that determine the unique processing qualities of wheat. Although it is a part of the superior HMW-GS pair (Dx5+Dy10), the contribution of the Dy10 subunit to wheat processing quality remains unclear. In this study, we elucidated the effect of Dy10 on wheat processing quality by generating and analyzing a deletion mutant (with the Dy10-null allele), and by elucidating the changes to wheat flour following the incorporation of purified Dy10. The Dy10-null allele was transcribed normally, but the Dy10 subunit was lacking. These findings implied that the Dy10-null allele reduced the glutenin:gliadin ratio and negatively affected dough strength (i.e., Zeleny sedimentation value, gluten index, and dough development and stability times) and the bread-making quality; however, it positively affected the biscuit-making quality. The incorporation of various amounts of purified Dy10 into wheat flour had a detrimental effect on biscuit-making quality. The results of this study demonstrate that the Dy10 subunit is essential for maintaining wheat dough strength. Furthermore, the Dy10-null allele may be exploited by soft wheat breeding programs.